Vaccination titres pre- and post-transplant in paediatric renal transplant recipients and the impact of immunosuppressive therapy - Höcker, Britta; Schnitzler, Paul; Rieger, Susanne; Krupka, Kai; Bruckner, Thomas; Fichtner, Alexander; Tönshoff, Burkhard (Pediatric nephrology, 2018)
Background: Avoidance of vaccine-preventable infections in paediatric renal allograft recipients is of utmost importance. However, the development and maintenance of protective vaccination titres may be impaired in this patient population owing to their need for immunosuppressive medication. Methods: In the framework of the Cooperative European Paediatric Renal Transplant Initiative (CERTAIN), we therefore performed a multi-centre, multi-national study and analysed vaccination titres pre- and post-transplant in 155 patients with serial titre measurements in comparison with published data in healthy children. Results: The percentage of patients with positive vaccination titres before renal transplantation (RTx) was low, especially for diphtheria (38.5%, control 75%) and pertussis (21.3%, control 96.3%). As few as 58.1% of patients had a hepatitis B antibody (HBsAb) titre >100 IU/L before RTx. 38.1% of patients showed a vaccination titre loss post-transplant. Patients with an HBsAb titre between 10 and 100 IU/L before RTx experienced a significantly (p < 0.05) more frequent hepatitis B vaccination titre loss post-transplant than patients with an HBsAb titre >100 IU/L. The revaccination rate post-transplant was low and revaccination failed to induce positive titres in a considerable number of patients (27.3 to 83.3%). Treatment with rituximab was associated with a significantly increased risk of a vaccination titre loss post-transplant (odds ratio 4.26, p = 0.033). Conclusions: These data show a low percentage of patients with positive vaccination titres pre-transplant, a low revaccination rate post-transplant with limited antibody response, and a high rate of vaccination titre losses.
Gesehen am 06.03.2020